ChemInform Abstract: Glycosyl Dithiocarbamates: β‐Selective Couplings Without Auxiliary Groups. Issue 36 (9th September 2014) - Padungros, Panuwat; Alberch, Laura; Wei, Alexander
Abstract This β‐selective glycosyl coupling methodology is also extended to a reiterative synthesis of tetrasaccharides.